Signaling by intracellular β2-adrenergic receptors regulates AMPA receptor trafficking and synaptic plasticity - Boram Lee; Xiaomin Xing; Erik A. Hammes; Zhuoer Zeng; Zoila M. Estrada-Tobar; Karam Kim; Kyle E. Ireton; Kwun Nok Mimi Man; Ariel A. Jacobi; Ruben A. Berumen; Justin C. Weiner; Ao Shen; et al. (Cell Reports)
Summary: Signaling by norepinephrine (NE) via adrenergic receptors (ARs) mediates attention, yet the underlying molecular mechanisms are largely unknown. AMPA receptors (AMPARs) form a complex with β2ARs, Gs, adenylyl cyclase, and protein kinase A (PKA) to augment AMPAR phosphorylation and, thereby, surface expression. We show that signaling by intracellular β2ARs is required for these effects and two different forms of long-term potentiation (LTP) that depend on β2AR signaling and phosphorylation of the AMPAR GluA1 subunit on S845. Inhibition of two NE transporters, the organic cation transporter 3 (OCT3) and the plasma membrane monoamine transporter (PMAT), impairs phosphorylation of the AMPAR GluA1 subunit on S845 by PKA, GluA1 surface insertion, both forms of LTP, and upregulation of miniature excitatory postsynaptic currents upon injection of NE into neurons. These results provide strong evidence for signaling by NE upon its transport into neurons in general and specifically in synaptic plasticity.